An Analysis of Classroom Management Implemented by EFL Teachers in the Tenth Grade of Kinesthetic Differentiated Learning Classes - Elsa Winarti Siregar; Dewi Syafitri; Ani Fiani; Andhi Dwi Nugroho (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This research investigates the classroom management implemented by English Foreign Language (EFL) teachers in kinesthetic differentiated learning classes at SMA Negeri 4 Lubuklinggau. The research aimed to analyze how teachers implemented the five aspects of classroom management: physical design, rules and routines, relationships, engaging instruction, and discipline. A qualitative case study was conducted with two experienced teachers, using observation checklists, semi-structured interviews, and documentation. Findings revealed that both teachers applied the components of classroom management, Teacher AR applied physical design, rules and routines, relationships, engaging and motivating instruction, and discipline effectively, although minimally decorated. In contrast, the teacher YF had many decoration in physical design, good relationship, and engaging and motivating learning, but decoration less organized, inconsistent rules and discipline. The results highlight that classroom management in kinesthetic classes is generally effective but requires improvement in consistency and classroom organization. The research emphasizes the importance of designing the classroom, implementing rules and routines, creating engaging and motivating instruction, fostering positive relationships, and applying discipline for kinesthetic learners. Keywords: Classroom Management, Differentiated Learning, English Teacher, Garret Theory. Kinesthetic Classes.